2004
DOI: 10.1081/cnv-120030210
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Immunohistochemical Phenotype in Breast Cancer and Its Lymph Node Metastatic Location

Abstract: At present, an important part of prognostic information, together with particular treatment strategies in breast cancer, take into account the immunohistochemical phenotype of the primary tumor location. However, the changing heterogeneity intrinsic to neoplastic cells in general leads us to consider the possibility that the expression of these proteins is modified during tumoral development and dissemination. With this hypothesis as a starting point, 60 patients with breast cancer were studied with immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…Tsutsui et al [13] found a high level of concordance in EGFR, c-erbB2 and p53 expression in primary tumors and matching metastatic axillary nodes. These results were not consistent with a study from De la Haba-Rodriguez et al [14], who found a concordant expression of ER, PgR, p53, HER-2 in primary tumors and metastatic lymph nodes in only about 40% of cases. In our study, although we report the paired expression in primary and matched node, we found lower levels of Bcl-2 and p53 expression (13 and 30%, respectively).…”
Section: Discussioncontrasting
confidence: 71%
“…Tsutsui et al [13] found a high level of concordance in EGFR, c-erbB2 and p53 expression in primary tumors and matching metastatic axillary nodes. These results were not consistent with a study from De la Haba-Rodriguez et al [14], who found a concordant expression of ER, PgR, p53, HER-2 in primary tumors and metastatic lymph nodes in only about 40% of cases. In our study, although we report the paired expression in primary and matched node, we found lower levels of Bcl-2 and p53 expression (13 and 30%, respectively).…”
Section: Discussioncontrasting
confidence: 71%
“…However, recent trials suggest hormone response rates can be as low as 30% [5,6]. Scant information is available regarding the correlation of primary hormone receptor status with metastatic hormone receptor status [7]. Most patients with ER or PR positive invasive breast cancers receive hormone treatment as part of adjuvant therapy [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, in our patient, the primary tumour lacked expression of oestrogen receptors. Modification of the expression of membrane proteins between primary and metastasis was studied by De la Haba-Rodriguez et al [4] in a series of 60 tumours. Sixty percent of the primary tumours presented a change in the expression of oestrogen and progesterone receptors, Ki-67 and HER-2 compared to the lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 99%